Food Standards and Welfare: A General Equilibrium Model with Market Imperfections - Tao Xiang; Jikun Huang; D'Artis Kancs; Scott Rozelle; Jo Swinnen (Katholieke Universiteit Leuven, LICOS Centre for Institutions and Economic Performance, 2010)
We analyze the effects of high standards food chains on household welfare taking into account general equilibrium effects and market imperfections. To measure structural production changes and welfare effects on rural and urban households, our model has two types of agents, five kinds of products and four types of factors. We calibrate the model using dataset from China. The simulation results show that how poor rural households are affected depends on a variety of factors, including the nature of the shocks leading to the expansion of high standards sector, production technologies, trade effects, spillover effects on low standards markets, market imperfections, and labor market effects.
Keywords: J11; J15; Y80; 330; Nahrungsmittelversorgung; Allgemeines Gleichgewicht; Unvollkommener Markt; Theorie; China